Ataxia in Patients With Bi-Allelic NFASC Mutations and Absence of Full-Length NF186 - Kvarnung, Malin; Shahsavani, Mansoureh; Taylan, Fulya; Moslem, Mohsen; Breeuwsma, Nicole; Laan, Loora; Schuster, Jens; Jin, Zhe; Nilsson, Daniel; Lieden, Agne; Anderlid, Britt-Marie; Nordenskjöld, Magnus; et al. (Frontiers in Genetics, 2019)
The etiology of hereditary ataxia syndromes is heterogeneous and the mechanisms underlying these disorders are often unknown. Here, we utilized exome sequencing in two siblings with progressive ataxia and muscular weakness and identified a novel homozygous splice mutation (c.3020-1G>A) in neurofascin (NFASC). In RNA extracted from fibroblasts, we showed that the mutation resulted in inframe skipping of exon 26, with a deprived expression of the full-length transcript that corresponds to NFASC isoform NF186. To further investigate the disease mechanisms, we reprogrammed fibroblasts from one affected sibling to induced pluripotent stem cells (iPSCs), directed them to neuroepithelial stem cells (NESCs) and finally differentiated to neurons. In early neurogenesis, differentiating cells with selective depletion of the NF186 isoform showed significantly reduced neurite outgrowth as well as fewer emerging neurites. Furthermore, whole-cell patch-clamp recordings of patient-derived neuronal cells revealed a lower threshold for openings, indicating altered Na+ channel kinetics suggesting a lower threshold for openings as compared to neuronal cells without the NFASC mutation. Taken together, our results suggest that loss of the full-length NFASC isoform NF186 causes perturbed neurogenesis and impaired neuronal biophysical properties resulting in a novel early-onset autosomal recessive ataxia syndrome.